THE IMPACTS OF STUDENTS’ PERCEPTION ON TEACHING STYLE AND CLASSROOM CLIMATE TOWARDS STUDENTS OF SMP MUHAMMADIYAH SURUH’S LEARNING MOTIVATION IN 2017 - Ida Zahara Adibah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Teachers' teaching styles are varied depending on teacher's creativity to create an interesting teaching-learning process. The use of variations in teaching is needed to overcome the boredom experienced by students in the learning process in the classroom, so that students have the motivation to learn. Student's learning motivation can also be generated from school atmosphere or classroom climate. If students have felt comfortable with a conducive classroom climate, there will be feed backin the form of behavior, one of which is the increase in student's learning motivation. This study aims to determine the effect of students' perceptions of teachers' teaching styles and school climate, eitherpartially or simultaneously, on student's learning motivation. This research includes explanatory research with survey approach. The population in this study is all students of SMP MUHAMMADIYAH SURUH Year 2017 and the the sample is obtained by using the technique"proportional stratified random sampling". Instruments in this study use questionnaires and documentation. While the data analysis technique use multiple regression analysis for validity test, Alpha Cronbach for reliability test, and multiple regression to determine the good influence, both partially and simultaneously, from the variables in this study. From the result of data analysis, it is known that: (1) student's perception on teaching style simultaneously influences student's learning motivation which is proven from t count = 3,349 and t table = 2,698; (2) school climate does not have an effect on student's learning motivation, which was proven from t arithmetic = - 0,482 while t table= 2,698; (3) students' perceptions about teacher's teaching style and school climate simultaneously influences the learning motivation, and it is proven from the analysis result obtained t value = 5,613 and significant t = 5,149 with significance level 1%; (4) the proportion of joint contribution betweenstudents' perception about teaching style and school climate has an effect on student's learning motivation of 21.1%, while 78.9% is caused by other variables not studied or outside this research; . Kata kunci: student’s perception, teacher’s teaching style, classroom climate, learning motivation